2019
DOI: 10.1080/08998280.2019.1674089
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic joint infection due to Mycobacterium moriokaense in an immunocompetent patient after a total knee replacement

Abstract: Nontuberculous mycobacteria (NTM) are a rare cause of prosthetic joint infection (PJI) that is documented to affect immunocompromised patients primarily. In this case report, we describe an immunocompetent patient with a rare case of PJI caused by Mycobacterium moriokaense after a total knee replacement. This patient is the eighth reported case of PJI caused by NTM and the first reported case in an immunocompetent individual. Because PJI caused by NTM is rare and difficult to treat, it is essential to include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A previous study showed that RGM is mainly responsible for PJI following primary TKA. 17) Multiple studies have already shown factors associated with PJI other than NTM infection following primary TKA. 18 19) Only a few case reports addressed this unusual cause of PJI.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that RGM is mainly responsible for PJI following primary TKA. 17) Multiple studies have already shown factors associated with PJI other than NTM infection following primary TKA. 18 19) Only a few case reports addressed this unusual cause of PJI.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed 39 articles, including 68 patients with PJI caused by NTM [18,21‐58]. Subsequently, all 68 patients were analyzed in detail.…”
Section: Literature Reviewmentioning
confidence: 99%